Multicultural and Gender Equity in The Mathematics Classroom The Gift of Diversity 1997 Yearbook - Trentacosta, Janet; kenney, Margaret J. (Reston, VA National Council of Teachers of Mathematics, 1997)
NCTM's 1997 Yearbook presents a vision of how a powerful mathematics program can be made available to all students, regardless of their gender, race, ethnicity, or socioeconomic situation. It features a variety of perspectives and diverse voices that address relevant issues and suggest possible models for achieving this goal.
Contents Preface . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . vii PART 1: ISSUES AND PERSPECTIVES 1. Mathematics for All Students: Access, Excellence, and Equity . . . 1 Lucille Croom Hunter College of the City University of New York, New York, New York 2. In Addition to the Mathematics: Including Equity Issues in the Curriculum . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 10 Marilyn Frankenstein University of Massachusetts—Boston, Boston, Massachusetts 3. Including African American Students in the Mathematics Community . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 23 Carol E. Malloy University of North Carolina at Chapel Hill, Chapel Hill, North Carolina 4. Teaching Mathematics in a Multicultural Classroom: Lessons from Australia. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 34 Jan Thomas Victoria University of Technology, Melbourne, Victoria, Australia 5. Class Matters: A Preliminary Excursion . . . . . . . . . . . . . . . . . . . . 46 Sarah Theule Lubienski Michigan State Univesity, East Lansing, Michigan PART 2: CLASSROOM CULTURES 6. Teacher Questions + Student Language + Diversity = Mathematical Power . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 60 Patricia F. Campbell University of Maryland at College Park, College Park, Maryland Thomas E. Rowan Montgomery County Public Schools, Rockville, Maryland 7. Students’ Voices: African Americans and Mathematics . . . . . . . . 71 Erica N. Walker Wake Forest University, Winston-Salem, North Carolina Leah P. McCoy Wake Forest University, Winston-Salem, North Carolina iv 8. Sí Se Puede, “It Can Be Done”: Quality Mathematics in More than One Language . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 81 Alfinio Flores Arizona State University, Tempe, Arizona 9. Making Mathematics Accessible to Latino Students: Rethinking Instructional Practice . . . . . . . . . . . . . . . . . . . . . . . . . . 92 Lena Licón Khisty University of Illinois at Chicago, Chicago, Illinois 10. Uncovering Bias in the Classroom—a Personal Journey. . . . . . . 102 Maryann Wickett Paloma Elementary School, Encinitas, California 11. Creating a Gender-Equitable Multicultural Classroom Using Feminist Pedagogy . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 107 Judith E. Jacobs Center for Education and Equity in Mathematics, Science, and Technology, California State Polytechnic University, Pomona, Pomona, California Joanne Rossi Becker San Jose State University, San Jose, California 12. Using Ethnomathematics as a Classroom Tool . . . . . . . . . . . . . . 115 Joanna O. Masingila Syracuse University, Syracuse, New York K. Jamie King Lemon Bay High School, Englewood, Florida PART 3: CURRICULUM, INSTRUCTION, AND ASSESSMENT 13. The History of Mathematics: A Journey of Diversity . . . . . . . . . 121 Frank Swetz Penn State Harrisburg, Middletown, Pennsylvania 14. Integrating with Integrity: Curriculum, Instruction, and Culture in the Mathematics Classroom . . . . . . . . . . . . . . . . . . . . 131 Ellen Davidson Simmons College, Boston, Massachusetts Leslie Kramer Haggerty School, Cambridge, Massachusetts 15. Integrating Mathematics with Community Service . . . . . . . . . . 142 Gwendolyn Clinkscales IS 218M School, New York, New York Claudia Zaslavsky Mathematics Education Consultant, New York, New York CONTENTS v 16. The Gift of Diversity in Learning through Mathematical Exploration . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 151 John C. Moyer Marquette University, Milwaukee, Wisconsin Jinfa Cai University of Delaware, Newark, Delaware Joan Grampp South Division High School, Milwaukee, Wisconsin 17. Dialectal Variations in the Language of Mathematics— a Source for Multicultural Experiences . . . . . . . . . . . . . . . . . . . . 164 Héctor Hirigoyen Dade County Public Schools, Miami, Florida 18. Integrating Mathematics and American Indian Cultures . . . . . . 169 Lyn Taylor University of Colorado at Denver, Denver, Colorado 19. Grounded Practice: Lessons in Anasazi Mathematics Emerging from the Multicultural Classroom. . . . . . . . . . . . . . . . 177 Clo Mingo University of New Mexico, Albuquerque, New Mexico 20. Know Thyself: The Evolution of an Intervention Gender-Equity Program . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 186 Trish Koontz Kent State University, Kent, Ohio 21. Assessment and Equity . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 195 Terri Belcher EQUALS, Lawrence Hall of Science, University of California at Berkeley, Berkeley, California Grace Dávila Coates EQUALS, Lawrence Hall of Science, University of California at Berkeley, Berkeley, California José Franco EQUALS, Lawrence Hall of Science, University of California at Berkeley, Berkeley, California Karen Mayfield-Ingram EQUALS, Lawrence Hall of Science, University of California at Berkeley, Berkel
Hard Cover
References: 248p.
Keywords: Mathematics - Study and teaching; Mathematics - Study and teaching - United States; Minority students - United States; Education - Mathematics; Sex differences in education